SEX HORMONE DERANGEMENT IN POST-MENOPAUSAL CHRONIC LIVER DISEASE PATIENTS: A CASE SERIES - Jiang, Chua Yi; Mun, Yong Shih; Liang, Yong Sy (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Healthy post-menopausal women will exhibit low estrogen, high follicle-stimulating hormone (FSH) and high luteinizing hormone (LH) levels. Abnormalities in these sex hormone levels will often trigger further investigations. Chronic liver disease is common in Malaysia, with chronic viral hepatitis as one of the most common causes. It is estimated that 1.17 percent of adult Malaysians have chronic hepatitis B (HBV) and 0.74% have chronic hepatitis C (HCV). High estrogen, low FSH and low LH are the common biochemical derangements among the patients with chronic liver disease. RESULTS The degree of post-menopausal sex hormone changes varied according to the degree of liver injury due to the underlying causes. In our case series, patients with higher Child-Pugh scoring and smaller liver size had higher estrogen and lower FSH and LH levels. CONCLUSION Sex hormone profiles for post-menopausal women with chronic liver disease show higher estrogen level with greater degree of liver cirrhosis. FSH and LH level then decrease as the degree of liver cirrhosis progresses.